Molecular diagnosis of echovirus 30 as the etiological agent in an outbreak of aseptic meningitis in Panama: May – June 2008 - Martinez, Alexander A; Castillo, Juan; Sanchez, Mirla C; Zaldivar, Yamitzel; Mendoza, Yaxelis; Tribaldos, Maribel; Acosta, Pablo; Smith, Rebecca E; Pascale, Juan Miguel (The Journal of Infection in Developing Countries, 2012)
Introduction: Aseptic meningitis outbreaks are commonly caused by viral pathogens with enterovirus a common etiological agent. Between May and June of 2008, an outbreak of 173 cases of aseptic meningitis occurred in the Chiriqui Province of Panama. Molecular techniques were used to identify the etiological agent. Methodology: Cerebrospinal fluid (CSF) samples from 75 patients were received at the Gorgas Memorial Institute for Health Studies. RNA extraction and one-step RT-PCR were performed on each sample to determine the presence of enterovirus. Thirty-four samples which were positive for enterovirus were subject to group-specific PCR, sequencing, and phylogenetic analysis to identify the etiological agent of the outbreak. Results: The CSF of 58 subjects was found positive for the enterovirus family using RT-PCR. Thirty-four samples were found to belong to the enterovirus B group. Phylogenetic analysis of four successfully sequenced samples revealed echovirus 30 as the etiological agent. Conclusion: Echovirus 30 is reported as the likely cause of an outbreak of aseptic meningitis in Panama, the first since the 1980s.